2019
DOI: 10.1016/bs.mie.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Phase-separated condensates of metabolic complexes in living cells: Purinosome and glucosome

Abstract: Sequential metabolic enzymes have long been hypothesized to form multienzyme metabolic complexes to regulate metabolic flux in cells. Although in vitro biochemistry has not been much fruitful to support the hypothesis, advanced biophysical technologies have successfully resurrected the hypothesis with compelling experimental evidence. As biochemistry has always evolved along with technological advancement over the century (e.g. recombinant protein expression, sitedirected mutagenesis, advanced spectroscopic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Then, 30 ng/ml EGF was supplemented to the Roswell Park Memorial Institute 1640 medium (RPMI 1640, Mediatech, Cat# 10-040-CV) that contains 10% dFBS. Note that FBS (Sigma, Cat# F2442) was dialyzed with Spectra Por 12 to 14,000 MWCO as previously described ( 27 , 28 ). ERK1/2 inhibitor (SCH772984, Selleckchem, Cat# S7101) and Akt inhibitor X (Sigma, Cat# 124020) were dissolved in DMSO (Sigma, Cat# 276855).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, 30 ng/ml EGF was supplemented to the Roswell Park Memorial Institute 1640 medium (RPMI 1640, Mediatech, Cat# 10-040-CV) that contains 10% dFBS. Note that FBS (Sigma, Cat# F2442) was dialyzed with Spectra Por 12 to 14,000 MWCO as previously described ( 27 , 28 ). ERK1/2 inhibitor (SCH772984, Selleckchem, Cat# S7101) and Akt inhibitor X (Sigma, Cat# 124020) were dissolved in DMSO (Sigma, Cat# 276855).…”
Section: Methodsmentioning
confidence: 99%
“…Human triple-negative breast carcinoma Hs578T (HTB-126) cell line was obtained from the American Type Culture Collection (ATCC). The cells were maintained in the RPMI 1640 medium supplemented with 10% dFBS and 50 μg/ml gentamycin sulfate (Corning, Cat# 61-098-RF) in a HeraCell CO 2 incubator (37 °C, 5% CO 2 , and 95% humidity) ( 27 ). The cells were also verified to be free of mycoplasma contamination by employing the Universal Mycoplasma Detection Kit (ATCC, Cat# 30-1012K) and authenticated by ATCC’s short tandem repeat profiling service.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a number of recent studies have shown that enzymatic rates can be increased by LLPS, including nucleation and assembly of actin filaments and microtubules 7,13,[21][22][23][24][25] , RNA autosplicing 26 , production of 3',5'-cyclic GMP-AMP 27 , carboxylation of ribulose-1,5-bisphosphate [28][29][30][31] and activation of Ras 32 . Given that condensates may selectively concentrate certain enzymes in a pathway and/or certain enzyme/substrate pairs, phase separation has also been invoked as a mechanism to provide specificity in signaling or metabolic networks through accelerating some reactions over others 1,33,34 . Since many substrates often compete for the same enzyme, especially in signaling networks, spatial separation could be used to bias some pathways over others.…”
Section: Introductionmentioning
confidence: 99%
“…Cell Culture: Human triple-negative breast carcinoma Hs578T cells (HTB-126) were obtained from the ATCC. Cells were cultured in the Roswell Park Memorial Institute 1640 (RPMI 1640, Mediatech, Cat# 10-040-CV) supplemented with 10% dialyzed fetal bovine serum (dFBS) (Sigma, Cat# F2442) (34,35) and 50 µg/ml gentamicin sulfate (Corning, Cat# 61-098-RF). Cells were then maintained in a HeraCell CO 2 incubator (37 °C, 5 % CO 2 , and 95 % humidity).…”
Section: Methodsmentioning
confidence: 99%